On the nonadditivity of the substituent effect in homo‐disubstituted pyridines. (3rd October 2016) - Hęclik, Karol; Dobrowolski, Jan Cz.
Abstract: The substituent effect in mono‐ and disubstituted pyridines was studied by means of the sEDA and pEDA substituent effect descriptors expressing the substituent effect on the σ‐ and π‐electron systems of the ring, respectively. The sEDA descriptors calculated for mono‐ or disubstituted pyridines can be presented as perfectly linear functions of either benzene or monosubstituted pyridine sEDA descriptors, respectively. For the pEDA descriptors, there are substantial deviations from linearity observed for both mono‐ and disubstituted systems. For the disubstituted systems, the nonadditivity of the pEDA descriptors is strongly pronounced for the substituents in the ortho‐ and para‐ positions to each other while it is only weak for the meta ‐located groups. For both mono‐ and disubstituted systems, there are correlations between charge at the nitrogen lone electron pair and the σ‐ and π‐electron withdrawing and donating properties of the substituent. In general, the electron charge increases with the increase of the σ‐electron donating ability but decreases with the increase of π‐electron donating ability of substituents. Again, the effects are more significant for substituents in the ortho‐ and para‐ positions than in the meta ‐position. The influence of the π‐electron properties of the substituent on the lone pair, belonging to σ‐electron system of pyridines, shows the presence of hyperconjugation effects in the substituted pyridines. The hyperconjugation can be also clearly observed in cross‐dependencies of the sEDA and pEDA descriptors. Abstract : Substantial deviations from linearity of the pEDA substituent effect descriptor for both monosubstituted and disubstituted pyridines are observed. They are strongly pronounced for the substituents in the ortho ‐position and para ‐position to each other, while the deviations are only weak for the meta ‐located groups. Cross‐dependencies of the substituent effect sEDA and pEDA descriptors demonstrate presence of hyperconjugation effects.